Balloon atrial septostomy and transition of subcutaneous to intravenous prostacyclin infusion for rescuing advanced right heart failure in idiopathic pulmonary arterial hypertension: a case report. Issue 3 (3rd May 2020) - Liang, Kae-Woei; Wang, Kuo-Yang
Abstract: Background: Intravenous (IV) prostacyclin analogues infusion and balloon atrial septostomy (BAS) are two important treatment options for managing advanced right heart failure in patients with idiopathic pulmonary arterial hypertension (IPAH). References and protocols are rare for dose titrations and transitions between subcutaneous and IV prostacyclin in functional Class IV IPAH patients. Balloon atrial septostomy is rarely done in very few expert centres. Case summary: A young female with IPAH who had received maximal medication including subcutaneous prostacyclin analogues injection was admitted due to advanced right heart failure. She received ascites drainage twice. Later, we directly switched the administration route of prostacyclin from subcutaneous to IV at a ratio of 1:1 instantly. Such rapid conversion led her into a state of profound hypotension and drowsy consciousness, which was resolved after escalating IV inotropics and reducing prostacyclin dosage. Five days later, she received BAS under the guidance of intracardiac echocardiography. Her urine output increased and dyspnoea improved gradually. Six months later, clinical worsening happened again with increase of ascites and dyspnoea. She underwent 2nd and 3rd session of graded BAS with relief of symptoms again. She received permanent transition to IV prostacyclin analogues infusions via a peripherally inserted central catheter after three sessions of BAS. Discussion: Balloon atrial septostomy is effective in stabilizing the critical right heart failure in IPAH patients but should be intended as a bridge to lung transplant procedure. Transition from subcutaneous to IV prostacyclin is helpful but needs to be titrated in proper aliquots and time intervals to avoid abrupt haemodynamic changes.